Genetic Engineering of an Industrial Strain of Saccharomyces cerevisiae for L-Malic Acid Degradation via an Efficient Malo-Ethanolic Pathway - Volschenk, H.; Viljoen-Bloom, M.; van Staden, J.; Husnik, J.; van Vuuren, H.J.J. (South African Journal of Enology and Viticulture, 2017)
The optimal ratio of L-malic and L-tartaric acid in relation to other wine components is one of the most important aspects that ultimately determine wine quality during winemaking. Winemakers routinely rely on the judicious use of malolactic fermentation (MLF) after alcoholic fermentation to deacidify and stabilise their wines. However, due to the unreliability of the process and unsuitable sensory modifications in some grape cultivars, especially for fruity-floral wines, MLF is often regarded as problematic and undesirable. Alternative methods for reducing the amounts of L-malic acid in wine will contribute to improving the production of quality wines in the future, especially in coolclimate regions. Most wine yeast strains of Saccharomyces are unable to effectively degrade L-malic acid, whereas the fission yeast Schizosaccharomyces pombe efficiently degrades high concentrations of L-malic acid by means of malo-ethanolic fermentation. However, strains of S. pombe are not suitable for vinification due to the production of undesirable off-flavours. Previously, the 5. pombe malate permease (mael) and malic enzyme (mae2) genes were successfully expressed under the 3-phosphoglycerate kinase (PGK1) regulatory elements in 5. cerevisiae, resulting in a recombinant laboratory strain of S. cerevisiae with an efficient malo-ethanolic pathway. Stable integration of the S. pombe malo-ethanolic pathway genes has now been obtained through the construction of a unique integration strategy in a commercial wine yeast strain. Co-transformation of the linear integration cassette containing the mael and mae2 genes and PGK1 regulatory elements and a multi-copy plasmid containing the phleomycin-resistance marker into a commercial Saccharomyces cerevisiae strain resulted in the successful transformation and integration of the malo-ethanolic genes. The recombinant 5. cerevisiae strain was successfully cured of phleomycin-resistance plasmid DNA in order to obtain malo-ethanolic yeast containing only yeast-derived DNA. The integrated malo-ethanolic genes were stable in 5. cerevisiae and during synthetic and grape must fermentation, L-malic acid was completely fermented to ethanol without any negative effect on fermentation kinetics and wine quality.